A Landscape Never Goes Out of Style. Diachronic Lexical Variation in Exhibition Press Announcements - Lazzeretti, Cecilia (HERMES - Journal of Language and Communication in Business, 2014)
The paper focuses on diachronic lexical variation in a professional textual genre which has gained growing importance over time in the fi eld of museum public relations and art discourse: exhibition press announcements (EPAs). The aim of the analysis is to investigate the language of EPAs from a diachronic perspective in order to identify word frequencies showing large increases or decreases, or stability in word frequencies. Baker’s (2011) method to distinguish variation over time across multiple corpora was applied and particular attention was placed on the presence of “lockwords”, i.e. words “relatively static in terms of frequency” (Baker 2011: 66). The analysis is carried out on a corpus of EPAs dating from 1950 to 2009 issued by American and British museums. The study reports on a number of trends relating to linguistic and cultural change of EPAs, including the emergence of new criteria in assessing the value of artists and artworks despite a certain consistency in terms of subjects, the shift from one-item to multi-item exhibitions and the preference for more vivid and straight-forward descriptions. For instance, the frequency of the noun landscape has remained stable over time, suggesting that this subject is particularly consistent in art displays, quite a sort of classic, that never grows old, while the artist’s career – a word showing a clear pattern of growth – has become particularly valuable over time for museum professionals in charge of exhibitions.